Notes on occurrence of the artichoke leaf-hair eriophyid mite (Eriophyes neocynarae Keifer) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The authors report the discovery of the eriophyid mite Eriophyes neocynarae Keifer on artichoke (Cynara scolymus L.) in eastern Sicily. The phytophagous species, new for Italian fauna, is only known in California (U.S.A.) and Egypt up to now. The morphology of different biological stages, some aspects of biology and systematics are dealt with.
Keywords: Acari; Eriophyidae; Cynara scolymus